PENGELOLAAN MODA TRANSPORTASI PADA PT. FAJAR RIAU WISATA DI KOTA PEKANBARU - Yoga Chairullah; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
PT. Fajar Riau Wisata is one of the modes of tourism transportation in Pekanbaru City, PT. Fajar Riau Wisata serves consumers from various cities according to the agreement. PT. Fajar Riau Wisata, which was once just a small business, has developed into one of the best modes of tourism transportation in Pekanbaru City, with all good services, capable bus units and also using the latest technology in today's transportation world. Therefore, this research was conducted to determine the development of PT. Fajar Riau Wisata as a mode of tourism transportation in Pekanbaru City and to find out the factors that influence the selection of PT. Fajar Riau Wisata as a mode of tourism transportation in Pekanbaru City. Selection of PT. Fajar Riau Wisata is inseparable because it has a bus fleet with good condition, complete facilities and excellent service. This study used a descriptive qualitative method. While the data collection techniques in this study used literature study, observation, interviews and documentation. Keywords: Tourism, Management, Modes of Transportation, PT. Fajar Riau Wisata.